Reconstruction of the papilla and immediate tattooing of the nipple-areola complex: the technique, results, and a literature review - Francisco Jose Fontenele Bezerra; Rosely Moraes Gonçalves de Moura (Revista Brasileira de Cirurgia Plástica, 2018)
INTRODUCTION: The reconstruction of the nipple-areola complex (NACRec) is the final stage of breast reconstruction; and tattooing the nipple-areola complex (NAC) is well established as effective, although not widespread among Brazilian plastic surgeons. We have shown a simple method of NACRec using skin flaps for the preparation of the papilla and immediate tattooing of the NAC, shortening the recovery of the patient and avoiding new surgeries. METHODS: We performed a retrospective study of patients submitted to NACRec in our private clinic, from September 2015 to December 2016. We also searched the Medline database from 2004 to 2016 for reports of diseases associated with tattooing. RESULTS: Twenty-six patients underwent 28 reconstructions of the nipple-areola complex, with a mean age of 48 years (ranging from 29 to 65 years), with no major complications, except for the irregularity in pigment absorption in eight reconstructions (28.5%). CONCLUSION: The use of tattooing techniques in the preparation of the nipple-areola complex proved to be effective, with minimal morbidity, and easy to perform, with high patient satisfaction rates, despite the need for a future touch-up to obtain the ideal shade.